Transgraniczne przemieszczanie odpadów: Nielegalne praktyki - Piątkowska, Bożenna (Studia Polityczne, 2024)
This article addresses the topic of transboundary illegal waste shipments in Poland, especially in the context of increasing urbanisation and industrial development leading to increased waste production. Despite the existence of international regulations such as the Basel Convention and the Bamako Convention, illegal practices still pose a serious threat to environmental protection and public health. Globalisation and economic growth are intensifying waste generation, which has led companies to seek cheaper methods of waste storage and disposal. These activities often run afoul of the law, leading to illegal waste shipments. Examples such as waste shipments to Pakistan or Ukraine detected by Polish inspection authorities illustrate the scale of the problem. Illegal storage and disposal of waste pollutes the soil, groundwater and air with toxic substances, with serious health consequences, such as respiratory diseases, cancers or birth defects. Unfortunately, despite the existence of robust international regulations, illegal waste shipments still pose a serious threat. In order to combat it effectively, it is necessary to deepen control and enforcement mechanisms, promote international cooperation and harmonise legislation within the European Union. Also, a thorough understanding of the issue and its impact is important to develop effective strategies to combat illegal waste shipments.